2020
DOI: 10.1021/acs.jafc.0c00947
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Herbicidal Activity of Novel Diphenyl Ether Derivatives Containing Fast Degrading Tetrahydrophthalimide

Abstract: To seek new protoporphyrinogen oxidase (PPO) inhibitors with better biological activity, a series of novel diphenyl ether derivatives containing tetrahydrophthalimide were designed based on the principle of substructure splicing and bioisomerization. PPO inhibition experiments exhibited that 6c is the most potential compound, with the half-maximal inhibitory concentration (IC50) value of 0.00667 mg/L, showing 7 times higher activity than Oxyfluorfen (IC50 = 0.0426 mg/L) against maize PPO and similar herbicidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Intensive efforts aimed at developing new herbicidal compounds or modifying existing ones are ongoing (9)(10)(11)(12)(13)(14)(15)(16). A wide variety of chemical compounds have demonstrated plant management activity including the indole derivatives 1 and 2 (12) which demonstrate photosynthesis inhibitory activity as well as compounds 3 (17) and 4 (18) which are plant growth inhibitors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive efforts aimed at developing new herbicidal compounds or modifying existing ones are ongoing (9)(10)(11)(12)(13)(14)(15)(16). A wide variety of chemical compounds have demonstrated plant management activity including the indole derivatives 1 and 2 (12) which demonstrate photosynthesis inhibitory activity as well as compounds 3 (17) and 4 (18) which are plant growth inhibitors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, benzoxazine derivatives were also used as medical or pharmaceutical intermediates in the synthesis of compounds with therapeutic interest [11]. In continuation of our effort to search for novel N-containing heterocyclic compounds with excellent bioactivities [12][13][14][15][16], herein we reported the synthesis and the crystal structure of substituted benzoxazine.…”
Section: Commentmentioning
confidence: 99%
“…13 Studies over the past decades have provided important information on interactions between HPPD enzymes and HPPD inhibitors: 1,3-dicarbonyl and aromatic moieties are an indispensable pharmacophore for potent HPPD inhibition. Many researches [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] in HPPD inhibitors indicated that modification of the aromatic moieties is an effective way to get new derivatives with excellent weed control.…”
Section: Introductionmentioning
confidence: 99%